Access to Justice for Wrongful Conviction Claimants in Sweden: The Final Legal Safeguard and Levels of (In)accessibility. Issue 3 (3rd July 2021) - Hellqvist, Sara
ABSTRACT: Although there is no common right to contest convictions in Europe, the prevention of miscarriages of justice plays a central part within the European legal framework and the formulation of human rights, and scholars have described the conviction of innocents as one of the biggest justice gaps in contemporary society. However, little attention has been focused on directing a critical gaze at the legal path individuals are obliged to take towards possible exoneration, i.e. the post-conviction review process. Drawing on legal claims relating to potentially wrongful convictions in Sweden, the aim of this article is to examine the accessibility of this remedy. The findings were studied through the lens of access-to-justice theory and illustrate the difficulties these persons have formulating a satisfactory application unless they receive legal support. This suggests that, in practice, having access to the review remedy is in many cases equivalent to having access to legal assistance. Yet convicted persons are generally not entitled to any legal support once the appellate procedure has come to an end. The worst-case scenario is that a lack of resources may result in potentially innocent persons remaining convicted for crimes they have not committed.